Impact of black point on wheat trade and its management - and A.A. PATEL, V.A. SOLANKI, N. AUGUSTINE (Indian Phytopathology, 2006)
yet the qualitative appearance of the grain, particularly, colour and lustre were affected that reduced the market price of wheat by 3.71 to 12.49 per cent in 5 to 50 per cent infected seed lots, respectively, compared to healthy seed lots. One spray of either mancozeb @ 0.25% or chlorothalonil @ 0.2% at hard dough stage, effectively managed the black point incidence. Positive correlation (r=0.66) of 1000 grain weight with disease incidence exhibited that bolder grains in spike were most vulnerable to black point development.